Examining the prevalence and antimicrobial resistance profiles of multidrug-resistant bacterial isolates in wound infections from Indonesian patients - Prastiyanto, Muhammad E.; Darmawati, Sri; Daryono, Budi S.; Retnaningrum, Endah (Narra Sains Indonesia, 2024)
The emergence of multidrug-resistant (MDR) infections in wounds is a significant public health issue. The aim of this study was to investigate the prevalence and antimicrobial resistance profiles of MDR bacterial isolates in wound infections. Through a cross-sectional study, 1035 bacterial isolates were collected from wound infection patients at Tugurejo Hospital in Semarang, Indonesia, over a three-year period (January 2020 to December 2022). Initial identification involved Gram staining and colony morphology assessment, followed by biochemical assays and antimicrobial susceptibility testing using the VITEK®2 Compact system. Gram-negative bacteria constituted the majority of isolates (60.77%, n=629). The predominant strains included were Staphylococcus spp. (30.92%, n=320), Escherichia coli (18.45%, n=191), and Klebsiella pneumoniae (13.04%, n=135). Notably, Gram-negative bacteria exhibited a significantly higher likelihood of MDR development compared to their Gram-positive counterparts (p<0.001), with Gram-negative bacteria having a 2.05 times higher probability of acquiring MDR. These findings underscore the urgent need for comprehensive surveillance of antimicrobial resistance patterns and the implementation of tailored antimicrobial stewardship programs to address the pressing public health challenge of MDR wound infections. Further research is warranted to elucidate the complex interplay of factors contributing to MDR development in wound infections, thereby informing targeted intervention strategies and improving patient outcomes.